Rantai Nilai dan Model Bisnis Media Televisi di TVRI - Alya Puteri Maharani; Chan Christine; Kevin Brassalie; Eko Suhartanto (Indonesian Business Review, 2021)
With the development of the creative industry in Indonesia, the world of television and radio in Indonesia must of course also have to develop for mutual progress. With so many media to enjoy entertainment and information, television and radio are still the choice of some Indonesian people. Nevertheless, television and radio are slowly being abandoned by the community because of other mediums that are present in this industry. In the television industry itself is being rivaled by a streaming platform that presents watching whenever and wherever, it becomes one of the challenges of the television industry to develop. The radio industry has also begun to compete with streaming platforms capable of delivering any song anywhere for its users. TVRI, as a company in Indonesia which is engaged in the television industry and is the first television station in Indonesia has its own way to survive and develop in one of the sub-sectors in this creative industry.